Hadith #4844 - Sunan Abi Dawud - Abdur Rahman bin Abi Sa'id al-Khudri عبد الرحمن بن أبي سعيد; Abu Sa'id al-Khudri; Ishaq bin Muhammad al-Ansari إسحاق بن محمد الأنصاري; Rabi' bin 'Abdur Rahman ربيح بن عبد الرحمن بن أبي سعيد الخدري; Salmah bin Shbyb سلمة بن شبيب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: One should not sit between two men except with their permission.
Grade: Hasan